Rediseño urbano del Parque la Quebrada Seca – Sector 2 del cantón Ambato - Valverde Casa, Juan Jose (2024)
Currently, the design of public recreational and cultural spaces plays a fundamental role in urban society. These areas allow social integration, foster a sense of belonging and strengthen community ties in a city. However, the underuse and deterioration of these spaces generate problems of insecurity and spatial disconnection. Therefore, the main objective of this project is to carry out a redesign that responds to the need to link the different stages of the La Quebrada Seca park. Within the methodology, it is expected to comply with a mixed approach, which will consist of conducting interviews to facilitate the investigation and analysis of spaces at the neighborhood level. In addition, observation sheets will be carried out to evaluate the current state of the park and thus identify the main deficiencies that must be corrected through a new design. Thanks to this analysis, in this case this need will be met thanks to the redesign of stage two, which will serve as a connecting element between two remaining stages, allowing the generation of an external relationship through new paths that manage to generate a better relationship with the immediate environment. and internal relations through the design of independent and complementary areas focused on a children's audience. With this redesign, it is expected that La Quebrada Seca park will become a space for meeting and coexistence, where the community can enjoy recreational and cultural activities, thus strengthening the social fabric and contributing to the well-being of the population.